Consumers' Awareness towards Organic Food Products in Coimbatore District - Jayanthi, M. (Indian Journal of Marketing, 2015)
The high growth of population and life expectancies during the twentieth century increased demand for food supplies in India. To meet this demand, the green revolution became the corner stone of India's agricultural achievement that transformed India from a food-deficient to a self-sufficient country. This self-sufficiency was achieved through an indiscriminate and excessive use of synthetic pesticides and chemical fertilizers. Overexploitation of natural and non-renewable resources, indiscriminate and irrational use of synthetic inputs like chemical fertilizers and pesticides for producing more and more food products has impaired the ecological balance and has put the health of the consumers in jeopardy. Therefore, the apparent contradiction of necessity for nutritional safety on the one hand and environmental sustainability on the other made it inevitable to resort to alternative food products like organic food products. However, the growth of the organic food sector is not upto the mark in India due to lack of awareness among consumers. Thus, this study analyzed the consumers' level of awareness about organic food products in Coimbatore District. A disproportionate stratified random sampling method was used, and a total of 550 respondents were surveyed by using a questionnaire. The results showed that 40.5% and 38.4% of the respondents were aware and partly aware about organic food products, and only 14% of the respondents were highly aware about the same. Thus, awareness acts as a crucial factor in changing the attitude of consumers towards organic foods.